Cultural and Economic Changes in Saudi Arabic and Their Impact on Saudi Arabian Women - Alqahtani , Beshaier Mohammed; Abouelwafa, Edyta Wolny- (Dirasat: Human and Social Sciences, 2025)
Objectives: The current study aimed to identify the attitudes of Saudi women towards the impact of current social and economic changes on the role of Saudi women and their contribution to the economic role within the family and society. It also sought to understand their perceptions of changes in roles within the Saudi family. Methods: To achieve the study’s objectives, a questionnaire was conducted involving 207 female students at Prince Mohammad Bin Fahd University. Results: The results revealed that Saudi women perceive a significant transformation in their role. However, religious teachings and traditions still impose limits on the development and openness of Saudi women in their social and economic roles. Additionally, the results indicated that 66% of the female participants in their twenties expressed a desire for mutual cooperation between spouses, noting that the role of women extends beyond motherhood and childbirth. Conclusions: The study recommended providing Saudi women with opportunities to engage in new roles within the framework of religious teachings, as they have demonstrated their capability to be leaders and balance their new roles with their social roles within the family.